Perencanaan Jalur Interpretasi Wisata Sejarah di Desa Blahbatuh, Kabupaten Gianyar, Bali - Yulianto, Albirahman; Kohdrata, Naniek; Sukewijaya, I Made (Jurnal Arsitektur Lansekap; Vol.9, No.1, April 2023DO - 10.24843/JAL.2023.v09.i01.p09, 2023)
Planning of historical tourism interpretation route in Blahbatuh Village, Gianyar Regency, Bali. Blahbatuh village is one of the villages in Blahbatuh district, Gianyar regency, Bali, with historical heritage in the form of historical stories and sites. Blahbatuh village starts to develop tourism programs that involves historic sites. One of tourism program that can be developed in Blahbatuh is a historical tourism that utilizing interpretation activity. This study has two objectives, that are to identify the potential historical sites as an attraction for tourist, and to plan interpretation route for historical tourism in Blahbatuh. This study uses survey method with planning stage from Gold which consist of preparation, inventory, analysis, synthesis, and planning. Descriptive analysis is applied in biophysics, and tourism aspects which consists of attraction, amenities, accessibility, and ancillary. Quantitative analysis is applied to measure the variable of tourist attraction. The result is formulated into an interpretation route plan, that is based on themes, space programming plan, and circulation plan. The interpretation route of Blahbatuh Village’s historical heritage is developed from the era of Bali ancient kingdom, to the colonial time within the village vicinity of Blahbatuh.